Implementasi Manajemen Pendidikan Multikultural di SMP Tumbuh Yogyakarta - Nurcholish, Dani (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2019)
This article wants to explain about the application of multicultural education management in SMP Tumbuh Yogyakarta. With the vision of the school "education for all", in the learning process teaches respect for diversity, tolerance and equal rights. These values of inclusiveness are the main foundation of the school curriculum. In detail, this text wants to reveal a number of things, namely: First, how multicultural leadership practices in SMP Tumbuh; Second, how is the management of multicultural curriculum planning; Third, how the multicultural-based teaching and learning process. This aspect is detailed in several ways, namely the management of education personnel, learning curriculum, management of relations with surrounding communities, and the spirit of multiculturalism that is able to inspire students to excel.